2014
DOI: 10.1080/00140139.2014.952351
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured and self-reported anthropometric information among firefighters: implications and applications

Abstract: This study evaluated the accuracy of self-reported body weight and height compared to measured values among firefighters and identified factors associated with reporting error. A total of 863 male and 88 female firefighters in four US regions participated in the study. The results showed that both men and women underestimated their body weight (−0.4 ± 4.1, −1.1 ± 3.6 kg) and overestimated their height (29 ± 18, 17 ± 16 mm). Women underestimated more than men on weight (p = 0.022) and men overestimated more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…In addition, it was observed that overall, our dataset was larger than the CAESAR dataset, which comprises American and European civilian populations. This agrees with previous research 43,44,68 that anthropometric characteristics of physically demanding occupations such as firefighters and law enforcement officers differ from general population characteristics. Firefighters are generally heavier when compared to the general population, with their weight at least 8 ∼ 10 kg higher than US civilians 43 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it was observed that overall, our dataset was larger than the CAESAR dataset, which comprises American and European civilian populations. This agrees with previous research 43,44,68 that anthropometric characteristics of physically demanding occupations such as firefighters and law enforcement officers differ from general population characteristics. Firefighters are generally heavier when compared to the general population, with their weight at least 8 ∼ 10 kg higher than US civilians 43 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, anthropometric shape models are required to develop head-mounted products that properly fit the head anatomical details, especially for first responders such as firefighters, law enforcement officers, and army personnel. Particularly, firefighters are heavier than the general population due to the demands of their job 43,44 , which require wearing heavier protective equipment and the ability to carry/drag people out of danger zones. A product developed using a civilian dataset may not be effective for occupation-specific populations, such as firefighters, law enforcement officers, and soldiers, who require unique anthropometric characteristics to meet their job-specific physical demands 45 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 38 studies had data on men (Supplementary Table I). Height was overestimated in the majority of the studies, with mean differences ranging from 0.3 cm to 2.9 cm [22,70], while SDs of the mean differences ranged from 1.1 cm to 7.2 cm [17,34]. Two studies, however, found no differences between self-reported and measured height [17,54], while in the Canadian Health Measures Survey conducted between 2007 and 2009, men underestimated their height by a mean of 1.2 cm [50].…”
Section: Resultsmentioning
confidence: 99%
“…At this time, most surveys are still paper based but online versions are also valid options which will likely become more prominent in the future [ 15 ]. Regardless of survey medium, both men and women are overwhelmingly seen overestimating their height and underestimating their weight [ 12 , 16 , 17 , 18 , 19 , 20 ]. This underestimation of weight is more pronounced in women [ 17 , 21 ] and in overweight individuals regardless of gender [ 17 , 18 , 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%